Improving EFTEM data using multivariate statistical analysis - Lozano-Perez, S (2008)
In this paper, the benefits of processing Energy-Filtered TEM (EFTEM) datasets with Multivariate Statistical Analysis will be described. These include: Isolation of the main sources of information, identification of features masked by noise and/or background and, more importantly, almost noise-free data reconstruction. © 2008 IOP Publishing Ltd.